The study of urban climate and the interface with the urban planning legislation: considerations from the case of Montes Claros - MG - Gomes, Patrícia Silva (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
This paper discusses the interface between the study of urban climate and urban planning legislation, with reference to the empirical results of a survey conducted for the case of Montes Claros. To this, initially draws a quick background about the Brazilian urbanization (with focus on urban planning and legislation) aiming to elucidate the axis history-explanatory of environmental conflicts associated with the occupation of urban land. In this context, shows the paths inaugurated for the Statute of City in relation to urban sustainability and emphasize the gaps left for this with regard to the incorporation of these issues to the urban planning legislation. On the other hand, discusses the theoretical aspects of urban bioclimatology, focusing on the impacts of the occupation on the climate, especially with regard to urban heat islands. The work assumes the presupposed that there is a correlation between the urban microclimates and the variables related to the use of the urban land. Thus, was create a empirical model associating the temperature relative humidity data obtained with three parameters related to the urban use of land, chosen from the theoretical frameworks, which are: 1 - proportion of green areas and impermeable areas, 2 - constructed density, 3 - urban geometry (through the Sky View Factor). The results were analysis through the technique of linear regression and showed a high correlation between the data, especially those directly related to urban legislation: constructed density and urban geometry. The correlations found were negative for green areas and positive for impermeable areas, highlighting the importance of vegetation in the decrease of temperature and humidity in spite of its retraction in dry seasons. The results show that there is interdependence between the variables. The urban heat island identified in the city confirms the theory of the phenomenon. Finally, discusses the forms to appropriate the results to the process of urban planning.